2003
DOI: 10.1063/1.1527925
|View full text |Cite
|
Sign up to set email alerts
|

Study of the benzene⋅N2 intermolecular potential-energy surface

Abstract: The intermolecular potential-energy surface pertaining to the interaction between benzene and N 2 is investigated theoretically and experimentally. Accurate intermolecular interaction energies are evaluated for the benzene-N 2 van der Waals complex using the coupled cluster singles and doubles including connected triples ͓CCSD͑T͔͒ method and the aug-cc-pVDZ basis set extended with a set of 3s3p2d1 f 1g midbond functions. After fitting the energies to an analytic function, the intermolecular Schrödinger equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…For the current study MP2/6-311++G­(d,p) theory was used and it gives a benzene + N 2 global minimum in which N 2 is parallel to the benzene plane and has a benzene + N 2 center-of-mass separation of 3.46 Å and a potential energy of −1.30 kcal/mol. These properties are in excellent agreement with experiment and higher level theoretical values. This structure is identified as orientation 1. Another structure was found, orientation 4, in which the internuclear axis of N 2 coincides with the C 6 axis of benzene.…”
Section: Computational Detailssupporting
confidence: 83%
“…For the current study MP2/6-311++G­(d,p) theory was used and it gives a benzene + N 2 global minimum in which N 2 is parallel to the benzene plane and has a benzene + N 2 center-of-mass separation of 3.46 Å and a potential energy of −1.30 kcal/mol. These properties are in excellent agreement with experiment and higher level theoretical values. This structure is identified as orientation 1. Another structure was found, orientation 4, in which the internuclear axis of N 2 coincides with the C 6 axis of benzene.…”
Section: Computational Detailssupporting
confidence: 83%
“…To calculate Raman scattering coefficients we make the assumption that intermolecular Raman bands gain their intensity via the ''libration-induced mechanism,'' 29,46,50,54,55 wherein cluster polarizability components are modulated during the course of an intermolecular vibration by virtue of the changing projection of the permanent polarizability components of monomer moieties along cluster-fixed axes. With this approximation and Eq.…”
Section: Rotational Constants and Raman Intensitiesmentioning
confidence: 99%
“…For Bz‐N 2 , which is a 5D problem in the rigid monomer approach and a 6D problem in our semirigid approach, Jaeger et al reported on minima, but not on TSs, on the IPES obtained at MP2/aug‐cc‐pVTZ level of theory. Lee et al determined an analytic function for the IPES on the CCSD(T)/aug‐cc‐pVDZ level including midbond functions in the basis set. For Bz‐H 2 O, that is 6D for the rigid monomer approach and 9D in our semirigid approach, previous studies include the work by Popelier et al, who found one minimum and two TSs using a Lennard‐Jones distributed multipole analysis potential.…”
Section: Resultsmentioning
confidence: 99%
“…These can be divided into two categories. Methods that rely on a fit which uses a grid of nonstationary points in a physically meaningful range of intermolecular coordinates also exist in an automatic fashion. Alternatively, other approaches make use of genetic or evolutionary algorithms in combination with a large variety of different methodologies allowing for the determination of minimum energy structures of molecular clusters .…”
Section: Introductionmentioning
confidence: 99%